The Influence of Language Identity on Students’ Learning Foreign Language Process - Syamsiyah Furotun, Nurus; Mustofa, Mutmainnah; Katrino, Iqbal; Pantja Putra, Suatmo (STAI Miftahul Ula Nganjuk, 2023)
Everyone has an identity and language is a sign of that. The associations in a person's environment, with whom they hang out, and where they learn can all have an impact on their identities. This research aims to explain the extent to which language is still used as a symbol of human identity. The language used every day can be a source of pride. Evidence of this pride can be seen from the development of its use which is dynamic. Language has a very important function to express cultural treasures. However, language over time has also developed. Challenges in learning a foreign language can also be influenced by the use of a person's everyday language. Students have their challenges in learning a foreign language, therefore it can be seen whether the everyday language they use has an influence when they learn a foreign language.